Chemical Exchange Saturation Transfer Magnetic Resonance Imaging Identifies Abnormal Calf Muscle–Specific Energetics in Peripheral Artery Disease. (19th July 2022) - Sporkin, Helen L.; Patel, Toral R.; Betz, Yaqub; Mathew, Roshin; Schumann, Christopher L.; Meyer, Craig H.; Kramer, Christopher M.
Abstract : Background: Peripheral artery disease (PAD) results in exercise-induced ischemia in leg muscles. 31 Phosphorus (P) magnetic resonance spectroscopy demonstrates prolonged phosphocreatine recovery time constant after exercise in PAD but has low signal to noise, low spatial resolution, and requires multinuclear hardware. Chemical exchange saturation transfer (CEST) is a quantitative magnetic resonance imaging method for imaging substrate (CEST asymmetry [CESTasym ]) concentration by muscle group. We hypothesized that kinetics measured by CEST could distinguish between patients with PAD and controls. Methods: Patients with PAD and age-matched normal subjects were imaged at 3T with a transmit-receive coil around the calf. Four CEST mages were acquired over 24-second intervals. The subjects then performed plantar flexion exercise on a magnetic resonance imaging-compatible ergometer until calf exhaustion. Twenty-five CEST images were obtained at end exercise. Regions of interest were drawn around individual muscle groups, and (CESTasym ) decay times were fitted by exponential curve to CEST values. In 10 patients and 11 controls, 31 P spectra were obtained 20 minutes later after repeat exercise. Five patients and 5 controls returned at a mean of 1±1 days later for repeat CEST studies. Results: Thirty-five patients with PAD (31 male, age 66±8 years) and 29 controls (11 male, age 63±8 years) were imaged with CEST. The CESTasym decay times for the whole calf (341±332 versus 153±72 seconds; P <0.03) as well as for the gastrocnemius and posterior tibialis were longer in patients with PAD. Agreement between CESTasym decay and phosphocreatine recovery time constant was good. Conclusions: CEST is a magnetic resonance imaging method that can distinguish energetics in patients with PAD from age-matched normal subjects on a per muscle group basis. CEST agrees reasonably well with the gold standard 31 P magnetic resonance spectroscopy. Moreover, CEST has higher spatial resolution, creates an image, and does not require multinuclear hardware and thus may be more suitable for clinical studies in PAD.